Recycling waste fresh paste through a dormancy—awakening method using CO2 as the awakener - Peiyuan Chen; Zijian Zong; Xinliang Qian; Yi Fang; Jin Li; Liping Wang; Jialai Wang (Case Studies in Construction Materials)
This paper proposed a dormancy—awakening method for the collection and recycling of waste fresh paste (WFP), generated from waste fresh concrete from concrete mixing plant. Sodium citrate was employed to put WFP into the state of dormancy with low rates of cement hydration; whereas gaseous CO2 was injected, serving as an awakener for the dormant WFP. Experimental results demonstrated that sodium citrate treatment effectively impeded the cement hydration of WFP, allowing a sufficient operational time for further accumulation and centralized processing. CO2 injection facilitated the in-situ generation of fine-sized CaCO3 within dormant concrete, providing nucleation sites for accelerated hydration of cement. Application of CO2 injection for 45 mins or 60 mins resulted in the restoration of 28d compressive strength of WFP to 99 % and 96 % of the blank mixture without dormancy treatment. This approach not only awakens dormant WFP through the in-situ generation of fine-sized CaCO3, but also achieves carbon sequestration, offering a sustainable and practical solution for recycling WFP and promoting eco-friendly construction practices.